Communicating Linguistics (Taylor & Francis, 2023)
Increasingly, academics are called upon to demonstrate the value of linguistics and explain their research to the wider public. In support of this agenda, Communicating Linguistics: Language, Community and Public Engagement provides an overview of the wide range of public engagement activities currently being undertaken in linguistics, as well as practically focused advice aimed at helping linguists to do public engagement well. From podcasts to popular writing, from competitions to consultancy, from language creation to community projects, there are many ways in which linguists can share their research with the public. Bringing together insights from leading linguists working in academia as well as non-university professions, this unique collection: